Linguistic and Political Worldview of Lesia Ukrainka (a Case Study of the Works by Dmytro Dontsov) (Linguostylistic Studies, 2021)
The article elucidates a linguistic, political, and ideological interpretation of Lesya Ukrainka’s creative work against the background of the socio-political picture of that time. The case study material of the article is the works of D. Dontsov, presented in a 10-volume edition and his separate books.The research has provided the creation of a linguistic and political portrait of Lesya Ukrainka, which has a pivotal significance for assessing D. Dontsov’s views. The  has proved that the thinker admired the encyclopedic writing of Lesya Ukrainka, emphasized the ideological content of her works, which formed national dignity, generated the revolting spirit, and promoted the desire to commit great deeds. D. Dontsov, like I. Franko, understood the pathos of the style of the poet, who was the first after T. Shevchenko to claim that Ukrainians have their own guiding force, their own national idea, which is unique by its nature.The embodiment of the struggle for the human soul in the language is a common and principal theme in the works of Lesya Ukrainka and D. Dontsov. The thinker uses the personomen Lesya Ukrainka to convey a certain event and to strengthen his opinion. An important research finding is a statement that the poet-prophetess adheres to her Ukrainian dream in ancient images to show that faith, struggle, and victory were already a sign of ancient heroic times. D. Dontsov also analyzes the defeat of the national liberation struggle, which was not an obstacle to the desire of Ukrainians for independence.The study argues that the worldview of Lesya Ukrainka is a model of invincibility for D. Dontsov. They both base their views on the concepts of their own people, own land, own way, own character, own truth.Stylistically colored are the biblical elements in the works of D. Dontsov, being enhanced by the personomen Lesya Ukrainka. Numerous examples illustrate the thinker's statement that the Scriptures know only the words “Yes” and “No” and those who do not know how to use them properly are people without faith and without love. The world history will throw them in the trash – a halfway is extremely dangerous.Characterizing Lesya Ukrainka in the aspect of linguo-personology is important for showing the political situation of the country and reproducing the national ideas of that time .
Keywords: personology (personomen); embodiment of the struggle in the language; category of ‘own’; biblical elements